Implementation and development of hospital-based health technology assessment in Poland from the perspective of hospital representatives: qualitative research - Furman, Maciej; Gałązka-Sobotka, Małgorzata; Kowalska-Bobko, Iwona (Frontiers in Public Health, 2024)
Introduction: The analysis of health technologies in Poland has so far mainly concerned drugs assessed by the Agency for Health Technology Assessment and Tariffication, which was established for this purpose. Due to the implementation of increasing and various forms of investment (hardware, diagnostic, and organizational) in hospitals, and the growing need to properly assess the costs of implemented solutions, Hospital-Based Health Technology Assessment (HB-HTA) began to develop. To implement HB-HTA in the Polish healthcare system, in 2019-2022 a project was carried out, the consortium members of which were: the National Health Fund, the National Institute of Cardiology in Warsaw and Lazarski University. Purpose of the study: Analyzing the possibilities of developing HB-HTA in Polish hospitals based on the experiences of the study participants. Presenting benefits facilities and barriers for HB-HTA units implementation to Polish hospitals. Methods: Qualitative analysis of in-depth interviews with the representatives of hospitals that participated in the HB-HTA project using the Nvivo12 program. A specially prepared questionnaire with questions regarding the pre-project, design, and post-project phases was presented to respondents from five of the seven hospitals participating in the pilot phase of the project, during which HB-HTA reports were prepared for selected medical technologies. The remaining two facilities that were invited refused to participate in the study. The Ethics Committee of the Jagiellonian University Medical College gave consent to conduct the study. Results: Hospital representatives indicate that the HB-HTA methodology allows for the assessment of investments in facilities based on appropriate data. Thanks to the project, employees of hospital units gained new skills, such as becoming familiar with literature reviews in medical bibliographic databases. However, HB-HTA in Poland has not been fully implemented because facilities do not obtain adequate benefits from the implementation of HB-HTA at the organizational and financial level. According to the study participants, the methodology itself should be modified to take into account the needs of the facility. Conclusions: The hospitals participating in the HB-HTA project are developing the field of analyzing how innovative solutions are implemented in their facilities, but not to the extent that was intended in the project design.